Response to select comments on the proposed paradigm shifts in running - Nigg, Benno M.; Mohr, Maurice; Nigg, Sandro R. (Current Issues in Sport Science (CISS), 2021)
Background: Six experts in the field of running-related research have critically addressed a proposal to abandon the paradigms of ‘impact force’ and ‘pronation control’ when investigating running shoes, running injury, and running performance. Further, these experts have commented on the suggestion of the new paradigms of ‘muscle tuning’ and the ‘preferred movement path’ that can be used to investigate questions related to running injuries and performance as well running shoe design and comfort. This publication synthesizes and addresses the main criticisms of the experts and describes future directions to further develop the ‘muscle tuning and ‘preferred movement’ paradigms.